Distributed team processes in healthcare services: a scoping review - Eid, Jarle; Brattebø, Guttorm; Jacobsen, Johan K.; Espevik, Roar; Johnsen, Bjørn Helge (Frontiers in Medicine, 2023)
Objective: High-quality healthcare services is delivered by teams rather than individuals and depends heavily on multidisciplinary cooperation between dispersed healthcare professionals. The aim of this scoping review is to identify common barriers and innovative applications of technology supporting team processes and patient safety, in geographically dispersed healthcare services.Methods: Studies were identified from searches in APA PsychINFO, Epistemonikos and Medline databases, from 2010 to 2023. A detailed search strategy was performed, and studies were included, based on prior established criteria. Results: Among the 19 studies that fulfilled our inclusion criteria, the majority (85%) were from Europe or North America, and most studies (53%) were quantitative, with a cross-sectional study design. Several reported observed distributed team processes in training and education. Most studies described barriers and detailed how innovative approaches and technological solutions were introduced to improve communication, coordination, and shared mental models in distributed healthcare settings. A small proportion of studies (16%) used health services data to examine interpersonal exchange and team processes. Conclusions: The scoping review offer recommendations to enhance future research on distributed team processes in healthcare services.